2017
DOI: 10.1111/1750-3841.13625
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Date (Deglet Nour) Seed Free and Bound Polyphenols by High‐Performance Liquid Chromatography‐Mass Spectrometry

Abstract: Date (Pheonix dactylifera L.) seeds are a valuable and abundant by-product with various potential food applications. Free polyphenols (FPPs) and bound polyphenols (BPPs) of date seeds from Deglet Nour variety grown in Australia were investigated using high-performance liquid chromatography-mass spectrometry. The FPP fraction contained the following main phenolic compounds per gram of date seed powder; procyanidin B1 (499.8 ± 7.8 μg), procyanidin B2 (288.6 ± 6.1 μg), catechin (167.6 ± 2.1 μg), epicatechin (39.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 44 publications
1
25
1
Order By: Relevance
“…In this study, two monomeric and three dimeric polyphenols from the seeds of Phoenix dactylifera L. were monitored in gastric and intestinal digestion stages. These polyphenols were identified in a previous study using HPLC-MS as date seeds extractable polyphenols (EPP) and included, catechin, epicatechin, procyanidin B1, procyanidin B2, procyanidin A2 (Sirisena et al, 2017). These were the most abundant date seed polyphenols, and those confirmed with HPLC-MS and internal standard spiking therefore were selected to be monitored in this digestion study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, two monomeric and three dimeric polyphenols from the seeds of Phoenix dactylifera L. were monitored in gastric and intestinal digestion stages. These polyphenols were identified in a previous study using HPLC-MS as date seeds extractable polyphenols (EPP) and included, catechin, epicatechin, procyanidin B1, procyanidin B2, procyanidin A2 (Sirisena et al, 2017). These were the most abundant date seed polyphenols, and those confirmed with HPLC-MS and internal standard spiking therefore were selected to be monitored in this digestion study.…”
Section: Resultsmentioning
confidence: 99%
“…Ferulic acid was detected at fairly high levels in DSP (140 AE 9.1 to 216 AE 6.3 lg g À1 DSP) and DSPY (372 AE 8.2 to 456 AE 10 lg g À1 DSP). Free ferulic acid has previously been detected in some date seed varieties (Al-Farsi & Lee, 2008), however, not in the Deglet nour (Habib et al, 2014;Sirisena et al, 2017). Ferulic acid is usually found esterified with hemicelluloses (Aura, 2008), and it has been reported that fibrebound ferulic acid is released in human colon by the action of human colonic microbiota (Kroon et al, 1997;Rondini et al, 2004).…”
Section: Colonic Fermentationmentioning
confidence: 99%
See 2 more Smart Citations
“…For the NEPP acid hydrolysis, the residue post-EPP extraction process under optimized conditions was collected and was used for the extraction of NEPP following the method described by [31]. The extraction process was conducted in the absence of a metal catalyst.…”
Section: Preparation Of Non-extractable Polyphenols (Nepp) Extractmentioning
confidence: 99%